Direct medical cost of liver cirrhosis in Vietnam - Khanh, Nguyen Duy; Hung, Nguyen Manh; Khoa, Dao Ba; Man, Tieu Tu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Introduction: Cirrhosis is one of the leading causes of death worldwide and also a substantial economic burden for patients, healthcare system and society. However, research concentrating on cost of cirrhosis treatment in Vietnam are limited. The aim of this study was to estimate the inpatient treatment costs of liver cirrhosis and influencing factors on costs in Vietnam. Methods: Descriptive cross-sectional study has been conducted based on retrospective data of all cirrhosis patient’s records in 2015 from two hospitals (HCMC Tropical Hospital and Bach Mai Hospital), satisfied inclusion and exclusion criteria. Descriptive and correlation analysis were performed with relevant statistical test (T-test, one-way ANOVA, correlation) and 95% confidence level. Results: The median cost of treatment per session was 6,064,104 VND (3,246,810 VND – 11,195,492 VND); the drug cost has the highest median value with 3,040,395 VND (843,309 VND – 6,411,334 VND). In the structure of treatment cost, health insurance covered the most and the drug costs accounted for highest proportion with the median value of 3,642,446 VND (1,805,001 VND – 7,326,606 VND). The median values of health insurance rates are comparable. The related factors on costs of treatment included the place of residence, the number of days in hospital, the stage and the complications of cirrhosis. A multiple regression model to forecast treatment cost has been built with R-square=0.460, p=0.000; following which the number of days in hospital is the strongest factor on treatment cost (β=0.31, p=0.000); followed by the Northern living place (β=0.131, p=0.000) and the stage of disease (β=0.038, p=0.000). Discussions: We only assess the treatment cost for cirrhosis but do not evaluate the expense for the whole process including many different treatment courses yet. Secondly, this study does not evaluate the outpatient treatment costs. Furthermore, the multiple regression model can only explain 46.0% of the change of converted cost with 03 factors: the number of days using sick-bed, the Northern area and the disease stage. Conclusions: With the rising trend of liver cirrhosis in Vietnam and the high cost of treatment, national health policies and medical programs should be considered.